PORTRAYING THE CONTENT IN THE TEXTBOOK ENTITLED “THINK GLOBALLY ACT LOCALLY” BASED ON CULTURAL VIEW - Syahputra, Dimas; El Walidayni Kau, Magvirah; Mamu, Rahmawaty (Berajah Journal, 2025)
This qualitative study examines cultural representation in the Indonesian EFL textbook "Think Globally Act Locally" for Grade 9 students. Employing a descriptive design and content analysis approach, the research applies the theoretical frameworks of Cortazzi & Jin (regarding cultural categories: Source, Target, and International Cultures) and Yuen (regarding cultural dimensions: Product, Practice, and Perspective). The findings reveal a conspicuous imbalance. Cultural representation is significantly dominated by Indonesian Source Culture, reflected in the use of local names, folklore, cuisine, and landmarks. While this aligns with the "Act Locally" directive, this dominance overshadows the inclusion of both Target and International Cultures, which are not only minimal but also presented superficially. Furthermore, the analysis of cultural dimensions indicates a heavy reliance on surface-level representations of Products, while understanding of Practices and, in particular, the underlying Perspectives or philosophical values of cultures is severely limited. The study concludes that the textbook's unbalanced approach risks constraining students' global outlook. Therefore, it recommends a more equitable and profound integration of diverse cultural categories and dimensions to effectively foster the intercultural awareness competence essential for navigating global dynamics.